THE The Influence of Animated Video Media on Adolescents' Knowledge about HIV/AIDS Prevention - Endah Purwanti Handayani; Eftyaningrum Dwi Wahyu Astutik; Hasnia Hasnia; Hardini Hardini (Indonesian Journal of Global Health Research, 2026)
To determine the influence of animated video media on adolescent knowledge about HIV/AIDS prevention. Method: Quasy Experiment research design or quasi-experiment with One Group Pretest Posttest Design. Data were collected using a questionnaire then data tabulation and data analysis were carried out.The pre-test value of the animated video media and leaflet groups obtained an average knowledge value that was not much different, namely 5.45 in the treatment group and 5.05 in the leaflet group. This means there was no difference in the average knowledge in the animated video media and leaflet groups before being given knowledge about HIV/AIDS. The level of knowledge of animated video media has an effect compared to leaflet media on HIV/AIDS knowledge. There is a difference in adolescent knowledge about HIV/AIDS before and after being given counseling with animated video media and leaflet media in adolescents.